2022
DOI: 10.3390/sym14112415
|View full text |Cite
|
Sign up to set email alerts
|

The Shadows of Regular Black Holes with Asymptotic Minkowski Cores

Abstract: We investigate the shadows cast by a sort of new regular black hole which are characterized by an asymptotic Minkowski core and sub-Planckian curvature. First, we extend the metric with spherical symmetry to the one of rotating Kerr-like black holes and derive the null geodesics with a circular orbit near the horizon of the black hole. Then, we plot the shadows of black holes with different values for the deviation parameter. It is found that the size of the shadow shrinks with the increase in the deviation pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In this work, we focus on the case of spherical regular BHs. It is natural to extend the current study to rotating case which will be more realistic from astrophysical viewpoint [83][84][85][86][87][88]. We would like to leave this for further investigations.…”
Section: Summary and Discussionmentioning
confidence: 95%
“…In this work, we focus on the case of spherical regular BHs. It is natural to extend the current study to rotating case which will be more realistic from astrophysical viewpoint [83][84][85][86][87][88]. We would like to leave this for further investigations.…”
Section: Summary and Discussionmentioning
confidence: 95%
“…The GCSV BH was introduced in [351][352][353], including work by one of us, as toy model of a regular BH in the sense of Bardeen, where the core is asymptotically Minkowski rather than de Sitter 33 : stated differently, the associated energy density and pressure asymptote to zero rather than to a final value determined by the effective cosmological constant of the de Sitter case (see also [131,[354][355][356][357][358][359][360][361][362]). While the GCSV BH is introduced in a purely phenomenological way, Simpson and Visser (SV) argued in [353] that this space-time is mathematically interesting due to its tractability (the curvature tensors and invariants take forms which are much simpler than those of the Bardeen, Hayward, and Frolov BHs), and physically interesting because of its non-standard asymptotically Minkowski core.…”
Section: Ghosh-culetu-simpson-visser (Gcsv) Regular Black Holementioning
confidence: 99%
“…Instead, the Kretschmann scalar curvature is always zero at the center and reaches its maximum value at a point between the center and the horizon. This distinction may result in observable effects in the future and has been theoretically investigated in [32,43]. It is found that the shadows of black holes with Minkowski cores have larger deformations than those with de-Sitter cores.…”
Section: Conclusion and Discussionmentioning
confidence: 93%